2018
DOI: 10.1590/s1679-45082018ao4214
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Ogawa-Kudoh and modified Petroff techniques for mycobacteria cultivation in the diagnosis of pulmonary tuberculosis

Abstract: Objective To compare the performance of the Ogawa-Kudoh method with the modified Petroff technique in diagnosis of pulmonary tuberculosis.Methods A total of 205 sputum samples from 166 patients with clinical suspicion or under pulmonary tuberculosis follow-up, seen at a public tertiary care hospital, from July 2014 to July 2016 were used. All samples were simultaneously processed using the Ogawa-Kudoh and modified Petroff decontamination methods, according to the recommendations of the Ministry of Health. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 14 publications
3
21
0
3
Order By: Relevance
“…To the best of our knowledge, this is the largest ever study (2,915 clinical samples and 717 diagnosed TB patients) to determine that the K-O swab method is at least as good as the P-LJ method for the isolation of M. tuberculosis colonies from either sputum or extrapulmonary clinical samples. We confirm the results of previous studies, developed with a relatively small number of 315, 784, 569, 75, and 205 sputum samples (8)(9)(10)(11)(12). For sputum samples, the K-O method had a slightly higher but statistically significant yield of M. tuberculosis-positive samples, indicating that the K-O method even outperforms the P-LJ method for tuberculosis diagnosis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To the best of our knowledge, this is the largest ever study (2,915 clinical samples and 717 diagnosed TB patients) to determine that the K-O swab method is at least as good as the P-LJ method for the isolation of M. tuberculosis colonies from either sputum or extrapulmonary clinical samples. We confirm the results of previous studies, developed with a relatively small number of 315, 784, 569, 75, and 205 sputum samples (8)(9)(10)(11)(12). For sputum samples, the K-O method had a slightly higher but statistically significant yield of M. tuberculosis-positive samples, indicating that the K-O method even outperforms the P-LJ method for tuberculosis diagnosis.…”
Section: Discussionsupporting
confidence: 87%
“…Before being introduced as an efficient and fast method for culturing mycobacteria, this so-called Kudoh-Ogawa (K-O) swab method needs to be evaluated to determine its yield in the isolation of mycobacteria in comparison with established WHO-approved methods. To the best of our knowledge, there are only six relatively small-scale studies in the international literature that have evaluated the K-O swab method for its performance and compared it with the Petroff decontamination procedure (7)(8)(9)(10)(11)(12). These studies, executed in Venezuela, Brazil, Gambia, Uruguay, and India, were performed with sputum samples, and in all studies, both methods had a similar diagnostic yield, supporting the implementation of the K-O swab method for the microbiological diagnosis of pulmonary TB.…”
mentioning
confidence: 99%
“…Similar studies performed in Brazil (in 1999, 2006, and 2018) and Peru (in 2007) also found significant differences between the contamination rates obtained with OK and with standard mycobacterial culture methods, again showing that the OK method is efficient in recovering mycobacteria and efficiently killing contaminants. 8 , 9 , 10 , 11 These results indicate the value of the OK mycobacterial method for diagnosis of pulmonary tuberculosis as a possible alternative for the NALC/LJ method.…”
Section: Discussionmentioning
confidence: 75%
“…5 As apresentações extrapulmonares (disseminadas ou não) são mais frequentes entre os indivíduos infectados pelo HIV, tornando mais prevalente o encaminhamento de casos suspeitos para serviços especializados ou de maior complexidade. 4 Embora o método OK tenha sido relatado como sensível e específico para M. tuberculosis na detecção de doença pulmonar (amostras de escarro), [19][20][21] comparações de seu desempenho com a abordagem LJ (padrão ouro) permanecem escassas. [22][23][24] No LACEN-MS, a abordagem OK tem se mostrado particularmente útil para o diagnóstico em minorias étnicas situadas remotamente, dado o baixo custo do método e facilidade de operação, sem comprometer a viabilidade micobacteriana na etapa de descontaminação.…”
Section: Discussõesunclassified
“…27 Só recentemente o método foi sugerido para outros regiões do país, para expandir a cobertura diagnóstica das apresentações pulmonares. 21 O diagnóstico confirmado por cultura se traduz em ganhos palpáveis na qualidade de vida, não só dos pacientes, mas também da comunidade, por agilizar a identificação e o tratamento de fontes bacilíferas, mesmo quando resistentes aos medicamentos. 5,21 O baixo custo, estimado em US $ 1,00 para cada tubo de meio de cultura, devido ao uso de glutamato de sódio em vez de asparagina, tem sido um fator determinante para o atual uso mais amplo do OK no Mato Grosso do Sul.…”
Section: Discussõesunclassified